2016
DOI: 10.18632/oncotarget.10166
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CHEK1, SLC26A4, c-KIT, TPO and TG as new biomarkers for human follicular thyroid carcinoma

Abstract: The search for preoperative biomarkers for thyroid malignancies, in particular for follicular thyroid carcinoma (FTC) diagnostics, is of utmost clinical importance. We thus aimed at screening for potential biomarker candidates for FTC. To evaluate dynamic alterations in molecular patterns as a function of thyroid malignancy progression, a comparative analysis was conducted in clinically distinct subgroups of FTC and poorly differentiated thyroid carcinoma (PDTC) nodules. NanoString analysis of FFPE samples was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 42 publications
6
36
0
Order By: Relevance
“…This characteristic implies the potential relationship between MOCS3 and MSI. Apart from such two functional substrate synthesis regulatory genes, TPO which is also in our optimal prediction gene list encodes a membrane‐bound glycoprotein and contributes to the synthesis of thyroid gland bioactive substances . Though not reported exactly in colorectal cancer, such gene has been reported to contribute to the pathogenesis of MSI by interfering DNA mismatch repair in multiple tumor subtypes like breast cancer, implying such predicted gene may also be a functional gene associated with tumor driving MSI.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic implies the potential relationship between MOCS3 and MSI. Apart from such two functional substrate synthesis regulatory genes, TPO which is also in our optimal prediction gene list encodes a membrane‐bound glycoprotein and contributes to the synthesis of thyroid gland bioactive substances . Though not reported exactly in colorectal cancer, such gene has been reported to contribute to the pathogenesis of MSI by interfering DNA mismatch repair in multiple tumor subtypes like breast cancer, implying such predicted gene may also be a functional gene associated with tumor driving MSI.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that SLS5A5 was also identified as a risk factor (OR: 6.15). SLC5A is widely expressed in human tissues, including thyroid tissue [ 59 61 ] and is frequently methylated in human cancers [ 33 36 ], including thyroid cancer [ 61 64 ]. The SLC5A Meta bias test and resulting Egger graph showed that there was no the publication bias for association between the methylation of this gene and thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…154 Along with these findings, temporal profiles of serum and skeletal muscle metabolites are strongly affected by the type of nutrients and by meal timing. 42,56,137,[161][162][163] Elegant mechanistic studies have provided molecular links between the circadian clock and cell cycle, suggesting a direct role for core clock proteins in regulating key components of cell cycle progression, tumorigenesis and DNA damage. 142 Perturbation of these rhythms leads to considerable cardiovascular problems including hypertension, which is often associated with metabolic diseases, and various other pathologies (Figure 2, right panel).…”
Section: When the Clock Goes Wrong: Circadian Misalignments In Humamentioning
confidence: 99%
“…159,160 Altered expression levels of individual core clock genes are | 7 of 14 DIBNER associated with the progression of oncogenic transformation, making these genes plausible candidates for diagnostic biomarkers. 42,56,137,[161][162][163] Elegant mechanistic studies have provided molecular links between the circadian clock and cell cycle, suggesting a direct role for core clock proteins in regulating key components of cell cycle progression, tumorigenesis and DNA damage. [164][165][166][167] Furthermore, emerging genetic and molecular studies suggest that alterations in molecular clock components are associated with depression, bipolar disease and other mood disorders.…”
Section: Goes Wrong: Circadian Misalignments In Human Pathologiesmentioning
confidence: 99%